2018
DOI: 10.1016/j.yjmcc.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A carvedilol-responsive microRNA, miR-125b-5p protects the heart from acute myocardial infarction by repressing pro-apoptotic bak1 and klf13 in cardiomyocytes

Abstract: In conclusion, these findings reveal a pivotal role for miR-125b-5p in regulating CM survival during acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 63 publications
(120 reference statements)
6
65
0
Order By: Relevance
“…MiR-125b-5p represses proapoptotic bak1 and klf13 in cardiomyocytes and protects the heart from AMI. 20) MiR-19a/19b could reduce MI-induced cardiac damage and protect cardiac function. 21) Despite the therapies of miRNAs in MI, there are still many miRNAs that act as a potential therapeutic target in MI.…”
Section: Discussionmentioning
confidence: 96%
“…MiR-125b-5p represses proapoptotic bak1 and klf13 in cardiomyocytes and protects the heart from AMI. 20) MiR-19a/19b could reduce MI-induced cardiac damage and protect cardiac function. 21) Despite the therapies of miRNAs in MI, there are still many miRNAs that act as a potential therapeutic target in MI.…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that miR-125b-5p acts as an ischemic stress protector after acute myocardial infarction, opposing cardiomyocyte apoptosis by repressing pro-apoptotic bak1 (a mitochondrial protein) and klf13 (a zinc finger transcription factor). 8 The increased expression of miR-125b significantly decreases infarct size and prevents I/R injury in the myocardium. 9 These reports may indicate that the specific temporal and spatial expression patterns of miR-125b-5p have different biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, miR-125b-5p is involved in the acute response to myocardial I/R injury and myocardial infarction. 8,9 miR-15a is increased in the brain after I/R injury or transient ischemia. [10][11][12] Genetic deletion or pharmacological inhibition of the miR-15a/16-1 cluster significantly reduced I/R brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that NLRC5 participates in the transformation and invasion of malignant cancer cells (18,19) and an increasing number of studies have found that NLRC5 is associated with non-immunological diseases (20). MiR-125b-5p is a known regulator of apoptosis in several types of cells (21)(22)(23). Recently, NLRC5 was reported to have a protective effect against heart disease (24).…”
Section: Lncrna Malat1 Prevents the Protective Effects Of Mir-125b-5pmentioning
confidence: 99%